A STUDY OF INTESTINAL PARASITES IN CHILDREN OF AN URBAN REGION WITH EXCELLENT SANITARY CONDITION REVEALS HIGH OCCURRENCE OF Blastocystis SPP - Martins dos Santos, Bianca; Augusto Soares, Felipe; Laryssa Rosa, Stefany; da Conceição Ferreira Gomes, Denise; Tetsuo Nagase Suzuki, Celso; Bertequini Nagata, Walter; Helena Venturoli Perri, Silvia; Franco Teixeira de Freitas, Fabio; Denise Saraiva Bresciani, Katia; Xavier Falcão, Alexandre; et al. (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Intestinal parasites are among the major causative agents of diseases that affect animals and humans, especially children. In view of this, the current study evaluated the occurrence of these parasitic agents in 737 children in an urban region with excellent sanitation condition of the city of Pedreira, São Paulo, Brazil. Fecal samples from the children were processed with the use of a technique of high diagnostic efficiency (TF-Test®). The diagnosis of these samples resulted in the detection of 557 parasitic structures among eleven genera of parasites, and of 46.4% (342/737) infected children. Blastocystis spp. was found in 69.60% (238/342) of the positive samples and the monoparasitism was accompanied by symptoms in 44 children. Furthermore, 67.8% (232/342) of the infected children had close contact with pets, suggesting a possible zoonotic transmission. Lastly, this study allowed to perform health education to the children, aiming the reduction of new intestinal parasitic infections.